Assessing and Mapping Reading and Writing Motivation in Third to Eight Graders: A Self-Determination Theory Perspective - De Smedt, Fien; Rogiers, Amélie; Heirweg, Sofie; Merchie, Emmelien; Van Keer, Hilde (Frontiers in Psychology, 2020)
The twofold aim of this study was to substantiate the validity of the Self-Regulation QuestionnaireReading Motivation and Self-Regulation Questionnaire-Writing Motivation for third to eight graders and to map motivational trends in elementary and secondary education students' academic and recreational reading and writing. More particularly, we adopted the innovative and coherent theoretical framework of the Self-Determination Theory to study qualitatively different motives for reading and writing and to examine the relationships between them. In total, 2,343 students from third to eighth grade were involved. Based on confirmatory factor analyses, a two-factor model, distinguishing between autonomous and controlled motivation, for academic and recreational reading and writing was confirmed in all grades. Furthermore, the scales were reliable, and the measurement models were invariant across students' gender and their general achievement level. Despite the absence of strong invariance for the measurement models across each of the different grades, we found evidence that students within the same grade level (i.e., middle elementary, upper elementary, and lower secondary grade) interpreted the SRQ-Reading and Writing scale items in a conceptually similar way. Factor correlations confirmed the interrelatedness of reading and writing motives, as well as strong associations between students' motivation to read and write in either academic and recreational contexts. Finally, concerning the motivational trends, the present results advert to a significant decline of student's autonomous motivation to read and write, both in and outside school. Accordingly, we point out that the late elementary and the lower secondary grades are crucial phases to engage students in motivating literacy activities. In light of these alarming results, we recommend future experimental research studies to focus on evaluating the effectiveness of instructional reading and writing activities that foster students' innate need for autonomy, competence, and relatedness.